On the role of peptide hydrolysis for fibrillation kinetics and amyloid fibril morphology. Issue 13 (13th February 2018) - Ye, Xinchen; Hedenqvist, Mikael S.; Langton, Maud; Lendel, Christofer
Abstract : Peptide hydrolysis determines the fibrillation rate and the morphology of amyloid-like nanofibrils formed by β-lactoglobulin at low pH. Abstract : Self-assembly of proteins into amyloid-like nanofibrils is not only a key event in several diseases, but such fibrils are also associated with intriguing biological function and constitute promising components for new biobased materials. The bovine whey protein β-lactoglobulin has emerged as an important model protein for the development of such materials. We here report that peptide hydrolysis is the rate-determining step for fibrillation of β-lactoglobulin in whey protein isolate. We also explore the observation that β-lactoglobulin nanofibrils of distinct morphologies are obtained by simply changing the initial protein concentration. We find that the morphological switch is related to different nucleation mechanisms and that the two classes of nanofibrils are associated with variations of the peptide building blocks. Based on the results, we propose that the balance between protein concentration and the hydrolysis rate determines the structure of the formed nanofibrils.